2020
DOI: 10.3389/fnins.2019.01421
|View full text |Cite
|
Sign up to set email alerts
|

Kaixinsan, a Well-Known Chinese Herbal Prescription, for Alzheimer's Disease and Depression: A Preclinical Systematic Review

Abstract: Alzheimer's disease (AD), the most common cause of dementia, is highly prevalent worldwide with no modifying therapy. Behavioral and psychological symptoms of dementia (BPSD) occur in most patients with AD, and depression is one of the most common AD-related BPSD. Kaixinsan (KXS) is an ancient Chinese herbal prescription widely used to treat dementia and forgetfulness. In this systematic review, we conducted a meta-analysis to assess preclinical evidence for the effects of KXS on cognitive impairment and depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 75 publications
0
23
0
Order By: Relevance
“…Meyer, Poria cocos (Schw.) Wolf, Polygala tenuifolia Willd, and Acorus tatarinowii Schott [ 203 ]. A chronic administration of KXS (338 or 676 mg/kg, 3 weeks, i.g.)…”
Section: Chm Effects On the Neuroendocrine-immune Networkmentioning
confidence: 99%
“…Meyer, Poria cocos (Schw.) Wolf, Polygala tenuifolia Willd, and Acorus tatarinowii Schott [ 203 ]. A chronic administration of KXS (338 or 676 mg/kg, 3 weeks, i.g.)…”
Section: Chm Effects On the Neuroendocrine-immune Networkmentioning
confidence: 99%
“…For understanding the mechanism of action of a TCM formula at the systems level, it is essential to integrate the molecular mechanism into the system-wide mechanism of action. The representative TCM formulas in depression treatment are, but no limited to, Xiao-Yao-San (Chen et al, 2008), Kai-Xin-San (Fu et al, 2020), Jie-Yu-Wan (Feng et al, 2018), Shu-Yu-San (Chen et al, 2012), Chaihu-Jia-Longgu-Muli-Tang (Li et al, 2011), and so on. CUMS, chronic unpredictable mild stress; CSDS, chronic social defeat stress; CMS, chronic mild stress; SDM, social defeat model; CORT, corticosterone; CUS, chronic unpredictable stress; WKT, Wistar Kyoto; LPS, lipopolysaccharides.…”
Section: The Hpa Axismentioning
confidence: 99%
“…Wolf (PO), and Acorus tatarinowii Schott (AT) [ 19 ]. As a classic formula, KXS has been applied in amnesia treatment for thousands of years [ 20 ] and displays profound therapeutic effect for dementia and depression in clinical trials[ 21 ]. Some researchers have found that KXS exerts cardioprotective effects in a myocardial infarction [ 22 ], and could ameliorate chronic fatigue syndrome by affecting the levels of inflammatory factors [ 23 ].…”
Section: Introductionmentioning
confidence: 99%